ROLE OF ETHICS IN BANKING SOE PERFORMANCE - Mochamad Muslih; Novita Anggraeni Tamba; Syania Kurniawan; Iis Sugianti (Management Research Studies Journal, 2020)
Ethics is very necessary in every profession. Ethics is part of governance. The purpose of this study is to study the influence of deontology ethics, virtue ethics, utilitarian ethics, and egoism ethics on the performance of banking SOEs. This research uses quantitative methods. The population is state-owned banking stakeholders. The sample is a former auditor and user of BUMN banking services. The sample was taken purposively. The results showed that deontology ethics did not significantly influence the performance of banking SOEs, virtue ethics did not significantly influence the performance of banking SOEs, utilitarian ethics did not significantly influence the performance of banking SOEs, and egoism ethics had a significant effect on the performance of banking SOEs.